Microforming - from basic research to its realisation - Engel, Ulf; Eckstein, Ralf (Journal of Materials Processing Technology, 2002)
The production of miniature parts is gaining importance due to the trend of miniaturization which is increasingly determining the development of products ranging from mobile phones and computers to medical products. The application of conventional manufacturing processes for the production of such microparts is possible, but there are problems that result from the small dimensions. This fact applies also in the field of metal forming, however, in the meantime many research projects in several countries could improve this situation. This paper gives a review of the problems associated with miniaturization, the way of solution starting from basic research, and the results showing the progress of microforming today. © 2002 Elsevier Science B.V. All rights reserved.
LFT Import::2019-07-16 (1677)
Keywords: Material behaviour; Micro-metal forming; Processes